Cumulative 10-year performance of endodontically treated teeth with prosthetic restorations of base metal alloy double crowns with friction pins: a retrospective study - Hinz, Sebastian; Bömicke, Wolfgang; Bensel, Tobias (Clinical oral investigations, 2023)
Double crowns · Friction pins · Root canal treatment · Post and core · Fracture rate · Complication rate